31 Adoption of a single-page best practice algorithm reduces unnecessary stroke risk and improves arrhythmia management decisions in patients with acute atrial fibrillation: improving patient safety at north middlesex university hospital. (June 2018) - Maclean, Edd; Golding, Daniella de Block; Maden, Samantha; Patel, Shreena; Joseph, Olaminposi; Boot, Jesca; Denning, Max; Rear, Roger
Abstract : Objectives: In response to a serious incident involving an atrial fibrillation (AF) associated stroke, a quality improvement project was established to examine and abrogate unnecessary thromboembolic risk in patients presenting with acute AF to London's North Middlesex University Hospital (NMUH). Methods: The presenting complaint was examined for 2105 consecutive medical admissions to identify 100 patients (4.7%) with acute AF. For each patient, 36 indices and performance indicators were collected and analysed against international standards and the collective best practice of the local Cardiology team. Deficiencies were identified throughout the inpatient experience, including documentation, risk stratification, anticoagulation and arrhythmia management decisions. With cross-specialty collaboration, a single-page AF management algorithm was subsequently established using sequential PDSA Methodology, and following its Introduction a further 100 consecutive patients with acute AF were analysed prospectively. Results: Algorithm implementation significantly reduced the proportion of patients exposed to unnecessary stroke risk (30% – >4%, p<0.0001); improved identification and documentation of thromboembolic potential (50% ->88%, p<0.0001), reduced incorrect drug decisions (12% ->2%, p=0.01), reduced contraindicated rhythm control (8% ->0%, p=0.007), and increased direct oral anticoagulant (DOAC) prescribing (38% ->86%, p<0.0001) over warfarin. There was a trend towards reduced mean inpatient stay (4.7 ->3.5 days, p=0.11). Conclusions: Using established quality improvement Methodology and cost-neutral multi-disciplinary expertise, this novel management algorithm has significantly improved the quality and safety of care for patients with acute AF at NMUH. Prospective analysis of long-term adverse outcomes is underway to establish morbidity or mortality benefit [completion date: May 2018].